The shawshank redemption - Darabont, Frank (Warner Brother, 2003)
Few movies capture the triumph of the human spirit as memorably as The Shawshank Redemption. Morgan Freeman and Tim Robbins star in this powerful nominee for seven Academy Awards (including Best Picture) based on a Stephen King Story. Freeman plays "Red" Redding, a lifer who knows the ropes at Maine's State Prison. Robbins' new inmate Andy Dufresne, a quit banker unjustly convicted of murder. Andy's indomitable will earn Red's friendship; his resourcefulness brings hope and change to the entire prison. Andy is full of surprises- and he saves his best for last. Written and directed by Frank Darabont (The Green Mile), The Shawshank Redemption is "an engrossing, superbly acted yarn" (Tom Charity, Time Out Film Guide).